2021
DOI: 10.1002/ajmg.a.62187
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype in 18 Chinese patients with Coffin‐Siris syndrome

Abstract: Coffin‐Siris syndrome (CSS, MIM# 1359200) is a multisystem congenital disorder characterized by coarse facial features, hypoplasia of the fifth digits and nails, and intellectual disability. It is a genetically heterogeneous condition caused by pathogenic variants in genes encoding proteins of the BAF (BRG1‐associated factors) chromatin modeling complex and its downstream transcriptional factor. To date over 220 CSS individuals with pathogenic variants found have been described in the literature. This case ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For example, the parents of Cases 4-7 appear to be considerately less severely affected than their offspring. Although sporadic cases of inherited variants from similarly affected parents [21][22][23] or variants inherited through (gonadal) mosaicism [7,[24][25][26][27] have been reported (Table S2), here we describe for the first time that a pathogenic, non-mosaic variant is inherited from a very mildly affected parent with normal IQ values (i.e., the father in Case 7). Unfortunately, the grandparents could not be tested in our cases with inherited variants.…”
Section: Variable Expressionmentioning
confidence: 72%
“…For example, the parents of Cases 4-7 appear to be considerately less severely affected than their offspring. Although sporadic cases of inherited variants from similarly affected parents [21][22][23] or variants inherited through (gonadal) mosaicism [7,[24][25][26][27] have been reported (Table S2), here we describe for the first time that a pathogenic, non-mosaic variant is inherited from a very mildly affected parent with normal IQ values (i.e., the father in Case 7). Unfortunately, the grandparents could not be tested in our cases with inherited variants.…”
Section: Variable Expressionmentioning
confidence: 72%
“…A comprehensive study of various databases and individual publications confirmed a complex spectrum of SMARCB1 mutations (Online Resources 1, 2) (Tsurusaki et al 2012 , 2014 ; Kleefstra et al 2012 ; Santen et al 2013 ; Wieczorek et al 2013 ; Gossai et al 2015 ; Tate et al 2019 ; Diets et al 2019 ; Filatova et al 2019 ; Sekiguchi et al 2019 ; Cheng et al 2021 ). These include approximately 900 different somatic cancer mutations (Tate et al 2019 ; COSMIC Cancer database, https://cancer.sanger.ac.uk/cosmic ), including whole gene deletions and point mutations such as SMARCB1 c.1148del/p.P383RfsX100 (COSM1057), as well as neurodevelopmental disorders such as intellectual disability with plexus hyperplasia and the Coffin–Siris syndrome.…”
Section: Resultsmentioning
confidence: 95%
“…CSS is caused by heterozygous pathogenic variants in several genes encoding subunits of the BRG-1 associated factors (BAF) complex, which participates in the chromatin remodeling process. Pathogenic variants in ARID1B (MIM 614556) are detected in about 51%-76% of CSS patients (Cheng et al, 2021); other genes less frequently mutated are SMARCA4 (MIM 603254), SMARCB1 (MIM 601607), ARID1A (MIM 603024), SMARCE1 (MIM 603111), SOX11 (MIM 600898), ARID2 (MIM 609539), DPF2 (MIM 601671), PHF6 (MIM 300414), SOX4 (MIM 184430), SMARCD1 (MIM 601735), SMARCC2 (MIM 601734), and BICRA (MIM 605690) (Alfert et al, 2019;Aref-Eshghi et al, 2018;Barish et al, 2020;Hempel et al, 2016;Hoyer et al, 2012;Mannino et al, 2018;Schrier Vergano et al, 1993;Wieczorek et al, 2013;Zawerton et al, 2019).…”
mentioning
confidence: 99%